Assessment of Water Stored in Washed Lubricating Oil Containers and Its Effects on Kidney and Blood Functions in Albino Wistar Rats - Nwaonyeche, Napoleon Chinedu; Amadi, Destiny Chidugam; Effiong, Patricia Daniel (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The aim of this study is to evaluate effects of water stored in washed lubricating oil container (engine oil) on the kidney and blood function of an albino Wistar rat. Four sampling groups were established, group1 was control while three other groups were experimental groups. Total of twenty four (24) matured albino Wistar rats were investigated and acclimatized for seven (7) days, before rats were grouped into four of six rats each in the groups. The first group (control) was placed on control water as source of drinking water for 21days while other groups (test) was placed on water stored in washed lubricating oil container (engine oil) for a period of 28 days. The rats were fed on commercial feeds, at the end of the experiment the rats were weighed and sacrificed by anaesthetizing in a container containing cotton wool soaked in chloroform. Samples collected were kidney and blood. ANOVA was used to calculate mean and standard deviation while statistical significance was assessed at 0.05 probability level using Tukey-tests(p<0.05). kidney and lipid function parameters investigated were urea, creatinine, potassium, sodium, chloride, bicarbonate, total cholesterol, triglyceride, high-density lipoprotein and low-density lipoprotein, followed by heamatological test, which involves PCV, Hb, RBC, WBC, Platelet, MCHC, MCH, MCV, Neutrophil, Lymphocyte, Eosinophil and monocyte. Slight increase was observed in most of the results while in blood test, little decrease was noticed in group2. So water stored in washed lubricating oil container should be discouraged for drinking, because drinking it for a long period may pose future risky to human health.